Compassionate communication: a scoping review - Julia, Grace Jacob; Romate, John; Allen, Joshua George; Rajkumar, Eslavath (Frontiers in Communication, 2024)
Empirical evidence from compassion literature reports the inherent difficulty in teaching compassion-related qualities and indicates the recent shift towards promoting interventions focusing on enhancing communication skills associated with compassionate care. Given the absence of a strong empirical and theoretical understanding of compassionate communication, the present scoping review identifies and integrates the definitions and theoretical approaches to compassionate communication based on the existing literature. 5813 records identified through an initial search in four databases (Scopus, Web of Science, PubMed & Science direct) combined with the 49 obtained through manual search, underwent screening based on PRISMA-ScR guidelines. 57 articles that met the eligibility criteria were finalised for narrative synthesis (which included a thematic analysis and content analysis). The review serves as a constructive critique of the contradictions and issues with empirical evidence on verbal and nonverbal compassion and portrays the concept to exist beyond its impact on the alleviation of suffering by describing compassionate communication in light of 1) cognitive aspects, 2) affective aspects, 3) behavioural/state aspects 4) relational aspects, 5) self-compassion, 6) mutuality, 7) individual-specific virtuous traits or values. The necessity for an integrative definition of compassionate communication and a theoretical framework that links the components of compassionate communication with its antecedents and outcomes is highlighted. The review is a valid and reliable source of guidance for future research on theory, education, and interventions on compassionate communication. The findings of the review can be interpreted in light of both contemporary and traditional communication theory, having practical implications for different domains of society (i.e., family, workplace relationships, business, and healthcare)